Depression and suicide risk in dermatological diseases - a review of the literature - Hordejuk, Michalina; Marczak, Aleksandra; Szymkiewicz, Karolina; Hyjek, Michał (Journal of Education, Health and Sport, 2022)
Introduction Depression can be an independent disease entity, but can also result from other somatic diseases. Psychodermatology is a scientific field that deals with the interactions between dermatology and psychiatry and psychology. It is estimated that psychiatric disorders may co-occur in up to 30-60% of people with dermatological conditions. Mood disorders of the depressive type are most common among this group of patients [1]. It is important that skin specialists pay attention to the mental state of their patients in their daily practice. Objective In our work, we would like to draw attention to the interplay between psychiatric and dermatological diseases. Methods A literature search was performed in the PubMed medical publication database using the following keywords: depression; dermatology; skin; somatic; psychiatry; psoriasis; atopic dermatitis; acnes vulgaris; suicidal risk. Results There is a proven risk of depression in patients with psoriasis, acne and atopic dermatitis. These diseases also increase the risk of suicidal thoughts. Conclusions Awareness among professionals and patients of the co-occurrence of these disorders is insufficient, which in some cases can lead to serious consequences for the patient and affect the effectiveness of treatment of both dermatological and psychiatric disorders.